2018
DOI: 10.1080/13602381.2018.1431250
|View full text |Cite
|
Sign up to set email alerts
|

Beyond ‘know-what’ and ‘know-how’ to ‘know-who’: enhancing human capital with social capital in an Australian start-up accelerator

Abstract: Beyond 'Know-What' and 'Know-How' to 'Know-Who'-Enhancing Human Capital with Social Capital in an Australian Start-up Accelerator This study investigates the enhancement of human capital with social capital in a start-up accelerator and how this integration affects the entrepreneurial learning experience. In particular, it examines the relative importance of the three components 'know-what', 'know-how' and 'know-who'. The study involved thematic analysis of semi-structured interviews with participants in an Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 109 publications
3
31
0
2
Order By: Relevance
“…This corroborates other work showing that the main benefit of accelerators is less about hard forms of transactional support such as finance and training (i.e. "know-how") and more about the enhancement of social capital or "know-who" (Seet et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This corroborates other work showing that the main benefit of accelerators is less about hard forms of transactional support such as finance and training (i.e. "know-how") and more about the enhancement of social capital or "know-who" (Seet et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…These types of transactional services are found in nearly all accelerators across a variety of spatial contexts (Bliemel et al, 2018;Goswami et al, 2018). However, most studies examining accelerators find that many start-ups obtain important relational benefits from being involved in these programmes (Seet et al, 2018). Recent empirical examination of accelerators has shown that a key perceived benefit from participation in an accelerator programme is the relational and social capital it confers upon accelerator participants (Seet et al, 2018;Goswami et al, 2018).…”
Section: The Nature and Dynamics Of Start-up Acceleratorsmentioning
confidence: 99%
“…Our findings indicate that intensive mentorship facilitates and promotes startups' performance. This result corroborates prior research indicating the key role of mentors in acceleration programs (Cohen et al, 2019;Qian, Mulas & Lerner, 2018) and their positive impact in terms of new knowledge acquisition (Battistella et al, 2017;Gonzalez-Uribe & Leatherbee, 2016;Hallen, Cohen & Bingham, 2016;Polo-García-Ochoa, 2020;Qian et al, 2018;Seet, Jones, Oppelaar & Corral de Zubielqui, 2018;Wise & Valliere, 2014). In line with other studies, our results show how learning from mentors enables dynamic capabilities generation resulting in better performance in terms of probability of getting funded (Ambrosini & Bowman, 2009;Hernández-Linares et al, 2018;Li & Liu, 2014;Tsai, 2001;Qian et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Além da preocupação com a experiência dos empreendedores envolvidos no processo de desenvolvimento de suas startups, é importante notar também a relevância do papel dos mentores e gestores dentro de um processo de aceleração, uma vez que a prática corporativa e diversos estudos mostram a importância no aprendizado e no desenvolvimento da rede de contatos de empreendedores, startups e empresas estabelecidas. Os mentores e gestores são também responsáveis pela condução do aprendizado em questões como conhecer a solução que a startup está propondo a fazer, como elas podem desenvolver essa solução e para quem ela deve vender e de que forma ela se relacionará em seu meio (SEET et al, 2018). Outro fator importante ao buscar entender a importância da experiência dos times envolvidos se dá em relação a troca de conhecimento e habilidades entre os participantes envolvidos no processo (WISE; VALLIERE, 2014).…”
Section: Estruturação Da Revisão Da Literaturaunclassified
“…das ideias propostas pelas startups para os demais públicos de interesse das empresas estabelecidas e, finalmente, pelo conhecimento da solução e do mercado de atuação(DROVER et al, 2017;KANBACH;STUBNER, 2016;WAGMAN, 2014;KOHLER, 2016;KUPP;MARVAL;BORCHERS, 2017;MILES et al, 2017;SCHILDHAUER, 2018;SEET et al, 2018).Empreendedores não devem ser confundidos com agentes que se dedicam apenas a gerenciar iniciativas existentes, seguindo regras e parâmetros predefinidos com riscos pessoais bem controlados e baixos(SAXENA;SETHI, 2006). Um empreendedor é um importante impulsionador da mudança econômica e da gestão, utilizando técnicas para…”
unclassified